Developing quality assessment elements for tree planting works / Jasasikin Ab Sani - Ab Sani, Jasasikin (Institute of Graduate Studies, UiTM, 2015)
Malaysia is experiencing a major change in landscape development. In relation to the aim of turning Malaysia into ‘Garden Nation’, various strategies have been mapped including the campaign of greening the country through optimizing the number of tree planted over the country. Millions of trees have already been planted and many more will be planted in order to achieve a target of twenty millions of trees by the year of 2020. Despite the fact that the campaign is successfully carried out, the issue of quality for tree planting work still need to be duly addressed. The government of Malaysia under the Quality Management System (QMS) programme through Construction Industry Development Board (CIDB) in the year of 2006, has established Quality Assessment System in Construction (QLASSIC) as a tool to measure the quality of construction work. QLASSIC is a system or method to measure and evaluate the quality of workmanship of a construction work based on the relevant approved standard…